Existence of customary law in Indonesian criminal law - Helmi, Muhammad Ishar; Pujiyono, Pujiyono; Zada, Khamami (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
Currently, the scope and regulation of the criminal law system which only recognizes written law is deemed unable to accommodate the various legal needs of indigenous peoples who are still alive today. This is due to the principle of legality of criminal acts which is oriented towards individual-liberalism, not the plurality of society. Therefore, recognizing acts that violate customary law within the framework of the national legal system is considered appropriate in meeting the legal plurality needs of indigenous communities. The rigidity and arrogance of the current legalistic view of criminal law is no longer able to respond to plurality and a sense of justice, especially for customary law communities, because the reality of indigenous people's lives shows that there are countless customary law provisions outside of the law, which continue to live and are obeyed in every vein. community group members. The research method used in this study is a normative legal research method with a socio legal research approach. The socio-legal approach is intended as an approach in legal research that is focused on studying legal phenomena from the perspective of social sciences. The research results state that the position of traditional justice institutions is actually in a state of existence and absence, on the one hand it is not recognized by the Indonesian positive legal system but there are practices of these traditional justice institutions. However, cases decided based on customary law can still be found in a very limited number of cases.